Optimization of Extraction and Quality Assessment Based on Physicochemical Properties of Carrageenan from Red Algae (Kappaphycus alvarezii) Origin of South Sulawesi Indonesia: A Recent Study - ., Syaharuddin; ., Subehan; Alam, Gemini; Rifai, Yusnita (Research Trends and Challenges in Physical Science Vol. 5, 2021)
One of the compounds that can be developed as raw material for drugs or excipients is carrageenan which can be obtained from the red algae Kappaphycus alvarezii. This species of red algae was chosen as the object of research because in addition to its high carrageenan content, this species is easily found in the waters of South Sulawesi Indonesia. This research was started with collecting, washing and processing the red algae, then carrageenan extraction was carried out using the modified extraction method. The calculation results repeatability and reproducibility show that the %RSD of both does not exceed 3%, therefore the carrageenan extraction method using technical ethanol precipitator and pro-analytical ethanol meets the requirements repeatability and reproducibility precision because it meets the Horwitz standard, which is a maximum RSD of 3%. The extracted products were separated, purified and dried to obtain carrageenan raw materials. Then, the products were analyzed physically and chemically, and also using spectrophotometry and chromatography to ensure that carrageenan obtained meets the quality standards as excipient raw materials in pharmaceutical preparations. The results obtained were that Kappaphycus alvarezii red algae raw material fulfil the quality of the Indonesian National Standard (SNI) and carrageenan produced meet the quality standards of carrageenan according to Food Agriculture Organization (FAO), Food Chemicals Codex (FCC) and European Economic Community (EEC).